Government, the private sector, and local communities in ecosystem restoration governance and practices - Yanto Rochmayanto (Indonesian Journal of Applied Environmental Studies, 2021)
Ecosystem restoration is not only a concern for countries such as Indonesia, but has become a global concern, as the UN has announced the Decade on Ecosystem Restoration for 2021-2030. Ecosystem restoration is an important way of restoring degraded landscapes, ensuring the sustainability of biodiversity, as well as being an effective pathway for reducing emissions in the land-based sector. Indonesia has committed to ecosystem restoration through national statutory law since 2004, although it is no longer explicitly listed in the Omnibus Las No. 11 of 2020 and Government Regulation No. 23 of 2021 on Forestry Stewardship. Indonesia has  demonstrated good progress in the implementation of ecosystem restoration in several priority provinces coordinated by the Peat and Mangrove Restoration Agency, as well as in initiatives led by the private sector. Although both involved rural communities in restoration activities, I propose here that an innovative ecosystem restoration business model is necessary to make their participation more financially attractive to local communities. This paper provides an analysis of  progress and the needs for ecosystem restoration improvement in Indonesia.Restorasi ekosistem tidak hanya menjadi perhatian negara-negara seperti Indonesia, tetapi telah menjadi perhatian global, karena PBB telah mengumumkan Dekade Restorasi Ekosistem untuk 2021-2030. Restorasi ekosistem merupakan cara penting untuk memulihkan bentang alam yang terdegradasi, memastikan keberlanjutan keanekaragaman hayati, serta menjadi jalur yang efektif untuk mengurangi emisi di sektor berbasis lahan. Indonesia telah berkomitmen untuk melakukan restorasi ekosistem melalui peraturan perundang-undangan nasional sejak tahun 2004, meskipun tidak lagi secara eksplisit tercantum dalam Omnibus Las No. 11 Tahun 2020 dan Peraturan Pemerintah No. 23 Tahun 2021 tentang Penatagunaan Kehutanan. Indonesia telah menunjukkan kemajuan yang baik dalam pelaksanaan restorasi ekosistem di beberapa provinsi prioritas yang dikoordinasikan oleh Badan Restorasi Gambut dan Mangrove, serta inisiatif yang dipimpin oleh sektor swasta. Meskipun sama-sama melibatkan masyarakat lokal dalam kegiatan restorasi, saya mengusulkan di sini bahwa model bisnis restorasi ekosistem yang inovatif diperlukan untuk membuat partisipasi mereka lebih menarik secara finansial bagi masyarakat lokal. Makalah ini memberikan analisis kemajuan dan kebutuhan perbaikan restorasi ekosistem di Indonesia.